Development of Android-Based Educational Media Application Related to Work Fatigue in Nurses - Deby Aulia Fandani; Widya Hary Cahyati; Sri Ratna Rahayu (Universitas Negeri Semarang, 2024)
In this era, science and technology are advancing significantly. The development of information and communication technology, along with the emergence of mobile devices, can benefit the fields of education and healthcare through applications designed as educational media. Work fatigue among nurses is a condition that must be promptly addressed and cannot be ignored, as it can affect their job performance and has many negative consequences. The purpose of this research is to develop an educational media application related to work fatigue in nurses. This study is a Research and Development of an Android-based educational media application. Product testing was conducted by evaluating the validity of the educational media with content experts, media experts, and users (nurses). The results of the product testing showed that the content experts gave an average validity score of 92.86%, categorized as very valid, while the media experts rated it at 94%, also categorized as very valid. In a small-scale trial with 5 nurses, the application received a score of 93.7%, categorized as very good, though there were revisions needed regarding the ease of login. After revisions, a limited-scale trial with 10 nurses resulted in a score of 98.7%, categorized as very good. Thus, the developed educational media application on work fatigue for nurses is highly valid and can be effectively used by nurses independently on Android devices.